The lysianassid genus Pseudambasia in Australian waters(Crustacea, Amphipoda, Lysianassidae, Lysianassinae) - Kilgallen, N. M.; Lowry, J. K. (Zootaxa, 2013)
Pseudambasia appears to be an Indo-West Pacific endemic, comprising mostly tropical and temperate species but also one from the New Zealand subantarctic. In this paper the genus Pseudambasia Stephensen is diagnosed against all other genera of the Lysianassinae. Six new species of Pseudambasia (P. dartnalli sp. nov.; P. lochi sp. nov.; P. ponderi sp. nov.; P. poorei sp. nov.; P. sheardi sp. nov.; and P. springthorpei sp. nov.) are described from Australian waters.